Using Auditory Characteristics to Select Hearing Aid Compression Speeds for Presbycusic Patients - Zhang, Yi; Chen, Jing; Zhang, Yanmei; Sun, Baoxuan; Liu, Yuhe (Frontiers in Aging Neuroscience, 2022)
Objectives: To investigate how hearing aid compression speeds (fast-acting and slow-acting) affect temporal modulation and speech-in-noise performance in presbycusic patients for pre-selection of optimal compression speeds. Methods: Twenty-four patients with unilateral or bilateral moderate sensorineural hearing loss who scored higher than 21 on the Montreal Cognitive Assessment (MoCA) test participated. The electrocochleogram (ECochG) results, including summating potentials (SP) and action potentials (AP), were recorded. Subjects’ temporal modulation thresholds and speech recognition at 4 individualized signal-to-noise ratios were measured under three conditions – unaided, aided with fast-acting compression (FAC) and aided with slow-acting compression (SAC). Results: The results of this study showed that modulation discrimination thresholds in the unaided (-8.14 dB) and aided SAC (-8.19 dB) conditions were better than the modulation thresholds in the FAC (-4.67 dB) condition. The speech recognition threshold (SRT75%) for FAC (5.21 dB) did not differ significantly from SAC (3.39 dB) (p = 0.12). A decision tree analysis showed that the inclusion of the AP, unaided modulation thresholds and unaided SRT75% may correctly identify the optimal compression speeds (FAC vs SAC) for individual presbycusic patients with up to 90% accuracy. Conclusions: Both modes of compression speeds improved a presbycusic patient’s speech recognition ability in noise. SAC hearing aids may better preserve the modulation thresholds than FAC hearing aids. The unaided modulation thresholds and unaided SRT75%, along with the measurement of AP, may help guide the selection of optimal compression speeds for individual presbycusic patients.